Conflicting Clinical Presentation of Infection with Clostridium botulinum and Clostridium perfringens in a 5-Month-Old Infant - Barbara Schaub, MD; Carolyn Luhman-Lunt, MD; Andrea Ott, MD; Maren Krüger, DSc; Martin Skiba, PhD; Sylvia Worbs, PhD; Brigitte G. Dorner, PhD; Michael Buettcher, MD; Martin B. Dorner, PhD (Journal of Pediatrics: Clinical Practice)
We present a 5-month-old infant with a 1-day history of poor feeding and sudden progression into generalized weakness including septic shock syndrome after consumption of homemade food. Botulism and sepsis symptoms could be explained by the presence of a neurotoxin-producing Clostridium botulinum and an acute infection with enterotoxin-producing Clostridium perfringens.